COMPARATIVE OUTCOME OF EARLY VERSUS STANDARD ORAL FEEDING AFTER EMERGENCY BOWEL SURGERY (The Research of Medical Science Review, 2025)
Objective: To evaluate the safety and efficacy of early oral feeding compared to standard postoperative feeding in adult patients undergoing emergency bowel surgery.Study Design: Randomised controlled trial.Place and Duration of Study: Department of Surgery, Gulab Devi Hospital, Lahore, over a period of six months following approval by the College of Physicians & Surgeons Pakistan.Methodology: Sixty adult patients aged 18 years or older undergoing emergency bowel surgery were enrolled and randomised into two equal groups: Early Oral Feeding (EOF) and Standard Oral Feeding (SOF). Patients with terminal malignancy, recent abdominal surgeries, gross contamination, bowel ischaemia, postoperative stomas, ASA grade IV or above, or pregnancy were excluded. EOF was initiated within six hours postoperatively and advanced to soft diet within 24 hours if tolerated, while SOF commenced after clinical resolution of ileus. Primary outcome was hospital stay; secondary outcomes included vomiting, feeding tolerance, and associations with demographic and clinical variables. Statistical analyses were performed using SPSS version 25.0. Parametric and non-parametric tests were applied as appropriate. A p-value <0.05 was considered statistically significant.Results: Mean hospital stay was significantly shorter in the EOF group (4.57 ± 1.1 days) compared to the SOF group (6.68 ± 1.5 days) (Mann-Whitney U = 107.0, p < 0.00001). Vomiting occurred in 23.3% of EOF patients versus 6.7% in SOF (χ² = 3.2, p = 0.074), with an odds ratio of 3.76 (95% CI: 1.04–13.65). Age was positively correlated with hospital stay (r = 0.43, p = 0.002). Early feeding remained an independent predictor of reduced hospital stay (β = -2.11, p = 0.001).Conclusion: Early oral feeding following emergency bowel surgery was associated with significantly shorter hospitalisation without increasing major complications. Incorporation of early feeding into routine postoperative protocols may enhance recovery and reduce healthcare burden, particularly in resource-limited settings.